In vitro study of antibacterial activity of the alga Sargassum oligocystum from the Persian Gulf - Tajbakhsh, S.; Pouyan, M.; Zandi, K.; Bahramian, P.; Sartavi, K.; Fouladvand, M.; Asayesh, G.; Barazesh, A. (2011)
Background and Objectives: With due attention to the development of drug-resistant bacteria, discovering of new antibacterial compounds is needed. Algae produce numerous bioactive substances which may have pharmacological properties such as antibacterial activity. The objective of this investigation was to in vitro study of antibacterial activity of brown alga Sargassum oligocystum collected along the Bushehr coast of Persian Gulf (south west of Iran). Materials and Methods: Hot water extract, cold water extract, and hot glycerin extract were prepared. The effect of the extracts were investigated on Staphylococcus aureus (ATCC 25923), Staphylococcus epidermidis (ATCC 14990), Pseudomonas aeruginosa (ATCC 27853), and Escherichia coli (ATCC 25922). Results: Hot water extract exhibited antibacterial activity against Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa. Cold water extract and hot glycerin extract did not show antibacterial activity on any of the four test bacteria. The minimum inhibitory concentration (MIC) of hot water extract for both Staphylococcus aureus and Staphylococcus epidermidis was 3.175 mg/ml. However, the MIC of this extract for Pseudomonas aeruginosa was 9.556 mg/ml. Discussion: In this study gram-positive bacteria were more susceptible to hot water extract than gram-negative bacteria. Extract of Sargassum oligocystum could be a candidate for purification and further in vivo studies.